Analiza faktora rizika i prediktivna efikasnost preloma senile osteoporoze na osnovu biohemijskih pokazatelja metabolizma kostiju: Predictive Factors for Senile Osteoporosis Fractures - Mao, Yufang; Li, Kanghua; Zhu, Bing; Long, Jiang (Journal of Medical Biochemistry, 2024)
Background: Osteoporosis is characterized by low bone mass and altered bone microarchitecture. Patients with osteoporosis are at significantly increased risk for fragility fractures, which ultimately suffer fractures. The occurrence and development of osteoporotic fractures are significantly associated with high mortality, reduced quality of life as well as comorbidities. Biochemical indicators of bone metabolism are important for assessing the risk of fracture occurrence. In this study, we aimed to investigate the risk factors for osteoporotic fracture in the elderly based on bone metabolism biochemical indexes and to analyze their predictive efficacy through relevant bone metabolism biochemical indexes. Methods: A total of 254 elderly osteoporosis (OS) patients diagnosed and treated in our hospital during May 2019 to April 2022 was randomly picked, of which 100 patients were finally chosen for subsequent analysis following the inclusion and exclusion criteria. Patients were divided into OS fracture group and non-fracture group according to whether they had OS fracture. The contents of bone mineral density (BMD) and bone metabolism biochemical indexes, including Dickkopf-1 (DKK-1), sclerostin (SOST), osteoprotegerin (OPG), osteopontin (OPN), osteocalcin (BGP) and 25 hydroxyvitamin d (25 (OH) D) were detected in lumbar L2 4 and left femoral greater trochanter. The correlation between bone metabolism and BMD was evaluated using Pearson analysis. The risk factors of OS fracture were analyzed using Multivariate logistic regression analysis. The predictive value of biochemical indexes of bone metabolism on the risk of OS fracture was analyzed using ROC curve. Results: The proportion of patients with age and lack of sunlight in the OS fracture group was significantly higher than that in the non-fracture group (P < 0.05). The BMD in lumbar L2 4 and left femoral greater trochanter of patients in the OS fracture group was lower than that of patients in the non-fracture group (P < 0.05). At 14 weeks and 16 weeks after surgery, the levels of DKK-1, SOST and OPN in the OS fracture group were higher than these in the non-fracture group, and the levels of OPG, BGP and 25 (OH) D were lower than these in the non-fracture group (P < 0.05). BMD in lumbar L2 4, BMD in femoral greater trochanter, OPG, BGP and 25 (OH) D were the protective factors (P < 0.05), and the age, lack of sunlight, DKK-1, SOST and OPN were the risk factors affecting OS fractures (P < 0.05). BMD in lumbar L2 4 was negatively correlated with DKK-1, SOST and OPN (P < 0.05), and positively correlated with BGP and 25 (OH) D (P < 0.05). 25 (OH) D was positively correlated with femoral greater trochanter BMD (P < 0.05). OPG, OPN, BGP and 25 (OH) D had certain predictive value for the occurrence of OS fracture with the areas under the curve (AUC) of 0.709, 0.761, 0.720 and 0.730 respectively. The combined detection of all indicators had the AUC of 0.940 (P < 0.05), which had a high predictive value for OS fracture. Conclusion: Biochemical indicators of bone metabolism were closely correlated with the risk of OS fracture and had a high predictive value as influencing factors for the occurrence of OS fracture. Therefore, an accurate combination of biochemical indices could reduce the risk of fracture in the elderly, thus facilitating the development of targeted treatment plans for elderly fracture patients.